ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTELLECTUAL CAPITAL DISCLOSURE DAN PENGARUH INTELLECTUAL CAPITAL DISCLOSURE TERHADAP MARKET CAPITALIZATION - Prabowo, Dhanindra; Purwanto, Agus (Diponegoro Journal of Accounting, 2015)
This research aims to analyze the influence of firm size, firm age, leverage, profitability, and independent commissioner on the intellectual capital disclosure and influence of intellectual capital disclosure on market capitalization.The population of this research are all real estate and property companies that listed in Indonesian Stock Exchange (IDX) during 2010-2012. The samples were selected using purposive sampling method and obtained eighty four companies being sampled. This research analyzes the company’s annual report using the method of content analysis. Data analysis used descriptive statistics, classical assumption test, and multiple linear regression analysis. The result of this study showed that firm size and profitability significantly influence to the intellectual capital disclosure. Meanwhile, leverage,firm age and independent commisioner , had no effect to the intellectual capital disclosure. And, Intellectual capital disclosure significantly influence to the market capitalization.